EFEKTIVITAS LAYANAN BIMBINGAN KARIER DALAM MENINGKATKAN KEMAMPUAN PERENCANAAN KARIER SISWA - Wirastania, Aniek; Lianawati, Ayong; Hartanti, Jahju; Jannah, Aiza Uslifatul; Arista, Bella (Universitas PGRI Adi Buana Surabaya, 2022)
Students who have good career planning are usually characterized by characteristics such as having (1) understanding of the world of work, (2) special interests and talents in a particular world of work, (3) personality and values ​​related to careers. Career guidance services are guidance given to students and focused on providing assistance, especially in planning, developing, solving various career-related problems, and providing an understanding of the work in a position. Based on the implementation of community service activities, a result is obtained that this career guidance and counseling service activity can improve the ability to carry out career planning properly according to the talents and interests of students.